Resistance of CNT film toughened composite laminates under high-speed impact: Experimental and numerical study - L.I. Zhouyi; L.I. Jiming; L.I.U. Yan; J.I.A. Pengcheng; C.H.A.O. Huan (Polymer Testing)
This paper conducted high-speed impact tests for the carbon fiber resin matrix composite laminates toughened by multi-walled carbon nanotubes (MWCNTs) interlayers. Numerical simulations were conducted based on the tests by using the cohesive model with rate sensitivity and CNT toughening mechanism. It shows that the FEM (Finite element method) model can effectively predict the impact behavior of CNTs interlaminar toughened composites under high-speed impact. The influence and mechanism of CNTs on materials under impact were revealed, and it was found that the addition of CNTs can help materials resist delamination during impact and ensure the integrity of the laminate structure.